SOCIAL PERCEPTION FOR A SCHOOL COUNSELOR FROM THE VIEWPOINT OF STUDEN TS OF INTERMEDIATE AND PREPARATORY SCHOOL - Hussain, Turaya Ali (Al-Adab Journal, 2020)
In recent years has increased the need for psychological services, including psychological counseling as a result of scientific progress and knowledge and to increasing conflicts and wars between the sons of the people in the world. The success of the counseling process depends basis mainly on the role of the counselor and the education and the offer of guided and success that is reflected through the great social Perception and clear educational guides and to have a clear picture and know for his work and his role by individuals generally those around it. So that social perception and as provisions and evaluation in the light of bias individuals and their values and principles, and it comes through people interacting with each other. To achieve this present study aimed to measure social perception for a school counselor by students of students of intermediate and preparatory school and for both genders and which amounted to (200) male and female students who were randomly selected and the application of choice for them after making honesty standards and fortitude to the test. The results found that the perception of male and female students' social and intermediate stages and prep is statistically significant and which is interpreted as weak and has come as a result of the poor performance of the educational counselor in educational institutions and schools. In light of this, the researcher recommended the necessity of activating the role of leader and his work from his studies specialist university and the need to include the application for a sufficient period of stress and oversight of the work of counselors in the intermediate and preparatory school and activating the role of the media as well as schools.